Early Detection of Fungicide Resistance Through Sensitivity Testing of Various Fungicide Active Ingredients and Genetic Variation of Downy Mildew-Causing Peronosclerospora maydis from Maize (Corn) Production Centers in Java, Indonesia - Adhi, Satriyo Restu; Widiantini, Fitri; Yulia, Endah (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2024)
Maize downy mildew disease in Java, caused by Peronosclerospora maydis, can cause yield losses of up to 100%. Disease management of downy mildew using synthetic fungicides has been reported to cause resistance to P. maydis. This study identified early fungicide resistance in P. maydis from several maize production centers in Java (Blitar, Kediri, Klaten, Cianjur, Garut, Jatinangor, Rancakalong, and Sukabumi) by examining fungicide sensitivity levels and detecting genetic variation. The study was conducted at the Laboratory of Biotechnology of Plant Protection, Department of Plant Pests and Diseases, Faculty of Agriculture, Universitas Padjadjaran from November 2018 to August 2019. The results showed that isolates from Blitar and Kediri (East Java) indicated resistance to metalaxyl and fenamidone. While in general, P. maydis isolates from West Java and Central Java still have sensitivity to metalaxyl, dimethomorph, fenamidone, and oxathiapiproline. Oxathiapiproline was the most effective fungicide in damaging P. maydis conidia in all locations. Based on the results of molecular identification, there is intraspecies genetic variation based on phylogenetic analysis.